Densidade de máximos e função de correlação em mecânica clássica e sinais biológicos - Bastos, Helena Christina Piuvezam de Albuquerque (2017)
Nowadays, preventive medicine is a very important subject, since many diseases can be treated and even cured when it is possible to catch them in their initial phase. Therefore many areas of knowledge, like biology, medicine, chemistry, and physics are using their tools to facilitate diagnosis. In this study, chaos and its relationship with signal density were used to add new mechanisms in the search for a more precise and fast diagnosis. Supporting the concept of chaos, testing the method, and connecting physics to biology, we ﬁrst look at the double pendulum, a classical mechanics example of chaos, ﬁnding its length of correlation. For biological signals, the ﬁrst signal analyzed was population density. Next, we study the signal produced by the Hodgkin-Huxley model of a giant squid axon, after it was simulated and acquired in databases. Then, we ﬁnd on electrocardiogram signals a pattern in the length of correlation and their peak density, which when applied to the analysis of the clinical exam may provide information that is going to facilitate the diagnosis.